2019
DOI: 10.3390/su11051294
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Green Attributes in Production Processes as Well as Their Impact on Operational, Commercial, and Economic Benefits

Abstract: This paper reports a second-order structural equation model composed of four variables: the green attributes before and after an industrial production process, the operating benefits, the commercial benefits, and the economic benefits. The variables are related by means of five hypotheses and are validated statistically with information obtained from 559 responses to a questionnaire applied to the Mexican maquila industry. The model is evaluated using the technique of partial least squares and the results obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…Referring to table 2, the significant barriers to GM were: -Short term costs, low level of demand, technological problems, firm's awareness, poor enforcement, uncertain benefits. Similar studies which come out with the same results were (Ariffin et al, 2015;Gandhi et al, 2018;Kumar & Singh, 2014;Mendoza-fong et al, 2019) Short term costs (Costs) were found to be significantly determining the application of GM at 1% significance level. A movement from the category of firms which do not perceive short term costs as barriers to GM to the ones which perceive short term costs as a barrier to GM, it decreases the probability of a firm to apply GM by 64.8% Holding other variable at their means.…”
Section: Barriers To Green Manufacturingsupporting
confidence: 74%
See 1 more Smart Citation
“…Referring to table 2, the significant barriers to GM were: -Short term costs, low level of demand, technological problems, firm's awareness, poor enforcement, uncertain benefits. Similar studies which come out with the same results were (Ariffin et al, 2015;Gandhi et al, 2018;Kumar & Singh, 2014;Mendoza-fong et al, 2019) Short term costs (Costs) were found to be significantly determining the application of GM at 1% significance level. A movement from the category of firms which do not perceive short term costs as barriers to GM to the ones which perceive short term costs as a barrier to GM, it decreases the probability of a firm to apply GM by 64.8% Holding other variable at their means.…”
Section: Barriers To Green Manufacturingsupporting
confidence: 74%
“…The GM paradigm helps to minimize the environmental impact of manufacturing processes and ensures improvement in pollution control, reduction in consumption of natural resources and produces a green brand image, (Barzegar, Rasi, & Niknamfar, 2018;Gandhi et al, 2018). Specifically, some of the ascertained benefits of implementing GM among others include; reducing waste through efficient use of energy and raw materials, enhancing productivity and increasing product yield through greater efficiency, increasing profitability and quality of products, reducing the risks of environmental accidents and avoiding regulatory compliance costs leading to insurance saving, (Mendoza-fong et al, 2019). Other studies which have confirmed the benefits of GM among others include:- Abdullah et al, 2015;Baines et al, 2013;Belekar, 2017. Practicing GM among both small and large manufacturers has been influenced by a number of drivers and barriers.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Other researchers have emphasized the significance of the development process, management system, organization, motivation, and competencies (Awan et al, 2021; Bhatia, 2021; Chen et al, 2020). Furthermore, authors have linked Industry 4.0 and sustainability benefits to fully use green processes to meet sustainability objectives (Asiimwe & de Kock, 2019; Mendoza‐Fong et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Mendoza-Fong et al [23] determined 24 attributes of green processes which determine the level of the green manufacturing implementation. These attributes include processes themselves, which support the sustainability benefits of green processes.…”
Section: Green Processes and Technologies Classification Discussionmentioning
confidence: 99%